Motivation in service companies: Contributions from psychosocial intervention - Deroncele Acosta, Angel; Anaya Lambert, Yumairys; López Mustelier, Rosendo; Santana González, Yorkys (Revista Venezolana de Gerencia, 2021)
The present study was carried out in the “Comandante Camilo Cienfuegos Gorriarán” Nickel Service Company with the objective of analyzing motivation and designing a psychosocial intervention program to strengthen it. It was developed from the socio-critical paradigm, mixed approach, research-action method; We worked with a non-probabilistic sample of eight workers who are preparing for directive-managerial activity, to whom a motivation scale consisting of three dimensions: psychological, labor and organizational was applied. It was found that motivation had a low behavior (in the psychological and organizational dimensions), and medium in the work dimension; a significant relationship between the dimensions was found. To enhance motivation, a program based on appreciative inquiry and the dynamics of psychosocial intervention in organizations was designed, evaluated by experts as remarkably adequate, as it has the potential to strengthen motivation from the enhancement of the sense of belonging with managerial activity , the management of positive expectations towards the management and the social projection of the managerial position.